Serotyping of Syrian Uropathogenic Escherichia coli with Adhesion Genes FimH & PapGII - Sayed, Naji; Salman, Hassan; Tahan, Zaher Samman (Iraqi Journal of Science, 2024)
Urinary tract infections (UTIs) are the most common infections caused mainly by Escherichia coli and the O-antigen and FimH & PapGII adhesion genes are among the most important virulence factors. The aim of this study was to investigate the prevalence of some O-antigen in uropathogenic E. coli (UPEC) and molecular characterization of the adhesion genes FimH & PapGII. 63 E. coli isolates (50.4% from total number of samples) were collected from urinary tract infection patients from July to October in 2021 and identified using molecular and biochemical tests. Seven antigenic types of uropathogenic E. coli were investigated, as well as the presence of FimH & PapGII genes in uropathogenic E. coli strains. The results indicated that the majority of UPEC belonged to serotypes O1, O2, O4, O6, O7, O18ac and O75 in varying proportions, where the O1 serotype was the most predominant, followed by O2, O6, O75, O7, O4 and O18ac respectively. The results of molecular tests showed the presence of the FimH gene in 52 isolates with a percentage of 82.50% and the presence of the PapGII gene in 19 isolates with a percentage of 30.15%. From the results we can conclude that the serotypes O1 and O2 had the most virulence role due to presence of the adhesion genes FimH and PapGII.